2023
DOI: 10.20884/1.bioe.2022.4.3.4593
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Streptomyces sp. SAE4034 Antioxidant and Antibacterial Compound and Its Inhibitory Mechanism on Staphylococcus aureus

Abstract: The genus Streptomyces is known as producers of bioactive compounds that have antibacterial and antioxidant properties. Streptomyces sp. SAE4034 was known to produce antibacterial compounds that can inhibit and kill pathogenic bacteria, including Staphylococcus aureus, but the group of antibacterial compounds and their inhibitory mechanisms were not yet known. The ability of Streptomyces sp. SAE4034 in producing antioxidants is unknown yet. This research aimed to determine the classification of antibacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, another Streptomyces sp. strain SAE4034 has slightly lower activity with an IC50 DPPH value of 32.14 µg/mL [33]. These results indicated that our potential Streptomyces sp.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, another Streptomyces sp. strain SAE4034 has slightly lower activity with an IC50 DPPH value of 32.14 µg/mL [33]. These results indicated that our potential Streptomyces sp.…”
Section: Discussionmentioning
confidence: 76%
“…QZS11 Soil Ethyl-acetate crude extract [210] Streptomyces sp.MA4 Soil Selenium nanoparticles [211] Streptomyces sp. Sae4034 Rhizosphere soil Alkaloid, terpenoid, flavonoid, and polyphenol [212] Streptomyces levis HFM-2 Human gut 2-Isopropyl-5-methyl-1-heptanol; 1-Octanol, 2-butyl-, 3-Octadecene and 3-Eicosene [213] Streptomyces sp. MUSC Streptomyces colonosanans MUSC 93J T Mangrove soil Ectoine synthesis gene [223] Streptomyces monashensis MUSC 1J T Mangrove soil phenolic compounds, pyrazines and pyrrolopyrazines, Benzoic acid, 9H-Pyrido[3,4-b]indole [224] 6.…”
Section: Streptomycesmentioning
confidence: 99%